Analyzing The Level of Knowledge, Awareness and Attitude of Muslim Students Towards Halal Medicine In Yogyakarta - Auratul Atifah Harbit; Hendra Ramadan; Siti Nur Azizah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to examine the influence of public knowledge, awareness and attitudes towards halal medicines. The sample for this research was 100 respondents selected using a purposive sampling method in Yogyakarta. Data was collected through questionnaires distributed via social media and analyzed using multiple linear regression. The research results showed that the variables of knowledge, awareness and attitude were 61.4% regarding the halalness of medicines. Meanwhile, other factors contributed 38.6%, the rest was influenced by other variables. So, the knowledge variable has an insignificant influence, while awareness and attitude have a positive and significant influence on the halalness of medicines. This shows that Muslim students tend to still have low knowledge regarding understanding the halal nature of medicines. Apart from that, awareness and attitude also have different positive influences on the halalness of medicines. These findings have implications for the government, pharmaceutical factories and related agencies to pay more attention to the halalness of medicines in an effort to maintain public health and public trust. On the other hand, this research also contributes to researchers in the pharmaceutical field by enriching the literature regarding factors that influence the halalness of medicines.